Technology for preparing fundamental scientific research works in sports pedagogy - Peredelskiy, A.A.; Dzhancharova, G.K.; Dzhancharov, T.M. (Theory and Practice of Physical Culture, 2026)
Objective of the study is the substantiation of a comprehensive hypothetico-deductive model of fundamental research in sports pedagogy. Methods and structure of the study. The research was carried out using the method of hypothetico-deductive profile-applied modelling, as well as methods of document analysis (doctoral dissertations in pedagogy over the past 45 years) and the method of expert assessment with the participation of 11 lecturers from various Moscow universities holding the academic degrees of candidates and doctors of the social-humanitarian sciences block. Results and conclusions. The comprehensive hypothetico-deductive model developed within the framework of the study makes it possible to overcome the limitations of narrow-profile approaches. The model provides a logically verified trajectory of cognitive movement from an intuitive image through the deductive derivation of concepts, field empirical processing, analytical interpretation to the creation and experimental verification of pedagogical technology. Thus, the application of the proposed model of comprehensive hypothetico-deductive research in sports pedagogy contributes to the generation of reliable knowledge, corresponds to the modern stage of integrative development of science and education, and also makes it possible to prepare scientific qualification works that meet the requirements of interdisciplinarity and practical effectiveness.